Utilization of Social Media in the Community Service Program: A Study from Jambi, Indonesia - Ginanto, Dion (Journal of Southeast Asian Islam and Society, 2024)
The Community Service Program (Kuliah Kerja Nyata - KKN) is one of the flagship programs of universities that provides students with experience and opportunities to serve the community. Through designed and implemented work programs, students can directly apply the knowledge learned in lectures to society. To promote, engage, and succeed in KKN programs, students, lecturers, and the community require communication tools to facilitate every activity agenda. One effective communication medium adaptable to current developments is social media, such as Instagram, Facebook, blogs, YouTube, and Twitter. Social media has become an effective tool in implementing education and community service processes. Studies on the use of social media in learning at schools and universities have been widely conducted by researchers (e.g., Hudson et al., 2020; Harris, 2020; Kuswardhani, 2020); however, evaluations of social media usage in community service activities remain limited. Therefore, this study aims to explore the use of social media in implementing the 2021 Community Service Program. The ultimate goal of this research is to provide input for communities, lecturers, students, and policymakers in their efforts to enhance the quality of community service programs in the form of KKN. Using semi-structured interviews and observations involving 10 students from three regencies in Jambi Province, this study finds that social media serves three primary functions for students in community service programs: (1) as a medium for positive campaigns; (2) to disseminate information about social movements; and (3) as a tool for accountability and transparency.